Legal Aid: Existing Law, Policies and Practices in Nepal - Lamichhane, Bimal Prasad (Journal of Political Science, 2019)
Legal aid is a system of providing free or inexpensive advice, assistance, or representation for those who cannot afford to pay for the services of professional lawyers mainly because of a difficult financial situation. The provisions of legal aid to the poor are based on humanitarian considerations and the main aim of these provisions is to help the poverty-stricken people who are socially and economically backward. It can be said that the spiritual essence of the scheme consists in investing law with a human heart to ensure immanence of social justice in the juridical order on the substantive and the procedural planes of law. In this article the author clearly presents the notion of legal aid, its relevance, institutions rendering legal aid services in Nepal and examines the Nepalese scenario, legal provisions, policies, practices as well as the problems of legal aid in Nepal.